(untitled) (The Journal of Theoretical Accounting Research, 2025)
The global population continues to rise, while agricultural productivity has not kept pace. Ensuring food security requires higher production supported by access to quality seeds, fertilizers, irrigation, and modern technology all dependent on adequate credit. This study examines the impact of farm loans on the crop productivity of small and marginal farmers in Telangana State, India, and tests the moderating effect of technology adoption. Beyond its economic focus, the research conceptualizes agricultural loans as financial mechanisms that enhance accountability, sustainable performance, and efficient resource use within a sustainability accounting framework. Data were collected using a convenience sampling method from selected districts of Telangana. Instrument validity and reliability were confirmed through pilot testing, Cronbach’s alpha, and sample adequacy tests (KMO and Bartlett). The proposed model was validated through Structural Equation Modeling (SEM) using Smart PLS. Findings reveal that agricultural loans significantly improve crop productivity, while technology adoption strengthens this effect. The integration of financial access and technology promotes sustainable and accountable agricultural outcomes. The study provides insights for policymakers to design credit systems aligned with farmers’ needs and promote responsible resource utilization through technological support. The research is limited to selected districts in Telangana State.